Modelling the role of successful influencer marketing in health awareness - Buglyó-Nyakas, Erzsébet; Gál, Tímea (Vezetéstudomány / Budapest Management Review, 2025)
89% of Hungary’s population, nearly 8.55 million individuals, use the internet regularly, which means more than 7 million Facebook and 3 million Instagram users in 2023 (KSH, 2022; STATISTA, 2023a, 2023b). For this reason, influencer marketing is a highly topical and innovative subject that significantly impacts the purchasing decisions of consumers who participate in online social platforms. This research aims to gain a deeper insight into the tools and techniques used in influencer marketing and how they influence consumers’ health awareness, using netnographic and in-depth interviews. Building on Pilgrim & Bohnet-Joschko’s research, the study will examine the messages conveyed by influencers, the communication strategies used and the consumers’ responses. The results include a process of influence and can contribute to a deeper understanding of the influencer marketing process by combining secondary and primary research experiences and provide an excellent basis for further studies.